Escape [compact disc, unabridged] - Delinsky, Barbara (Random House, Inc., 2011)
Emily Aulenbach is thirty, a lawyer married to a lawyer, working in Manhattan. An idealist, she had once dreamed of representing victims of corporate abuse, but she spends her days in a cubicle talking with victims of tainted bottle water and she's on the bottler's side.